THE THE EXISTENCE OF MOTHER LANGUAGE IN TORAJA COMMUNITY IN JAYAPURA PAPUA: EKSISTENSI BAHASA IBU PADA MASYARAKAT TORAJA DI JAYAPURA PAPUA - Mariah Anggreni; Muhammad Suryadi (Jurnal Kata, 2024)
This study aims to see the existence of the use of the mother tongue by the Toraja people living in the Abepura sub-district, Jayapura city, Papua through the choice of language and the language attitude used. The research method uses qualitative descriptive with the research subjects being 4 families of Toraja descent who have lived in the housing behind the Abepura Koramil for more than 20 years. Data collection using questionnaires and in-depth interviews online. The data analysis technique uses the model from Miles and Huberman (1994) with a language maintenance and shift approach. Fasold's theory (1984) is a reference for the analysis of language selection and language attitude theory from Garvin and Mathiot (1968) and Krech (1988). The results show the maintenance of the mother tongue in the family and neighbor domains, but shifts to using Papuan Malay in the realm of friendship, and Indonesian in the realm of work. The informants who are parents aged 49-55 years old and the second first child aged 28-34 years old tend to maintain their language and showed a positive attitude in using their mother compared to the second or third child aged 21-25 years old who understood the norms of using the Toraja language but were not loyal and proud of their mother tongue.